Optimal land use under environmental and economic approaches - Restrepo Estrada, Camilo; Alviar Ramírez, Mauricio (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
Soil losses resulting from human activity have negative impacts in terms of loss of productivity and therefore income. In that sense, there is an overcost associated with the increased use of fertilizers as a result of the decrease of nutrients and organic carbon accumulation. The main objective of this paper is to develop a methodological tool to assess the optimal land use from an environmental and economic point of view. To observe potential variations of soil loss and potential economic benefits in the Negro river watershed, the Revised Universal Soil Loss Equation (RUSLE) methodology and economic valuation of market prices was used coupled with Geographic Information Systems (GIS) tool (ArcGIS 9.3). The obtained results with the GIS model are processed using multi-criteria evaluation techniques. Results show that land use in 2007, even though it represents greater economic benefit for farmers and peasants in the short term, it is not an economical and environmental optimal allocation in the long-term.